Potentiometric cholesterol biosensing application of graphene electrode with stabilized polymeric lipid membrane - Nikoleli, G.-P.; Ibupoto, Z.H.; Nikolelis, D.P.; V. Likodimos; Psaroudakis, N; Tzamtzis, N.; Willander, M.; Hianik, T. (Central European Journal of Chemistry, 2013)
A novel potentiometric cholesterol biosensor has been fabricated through the immobilization of the stabilized polymeric lipid membrane onto graphene electrode. The stabilized polymeric lipid membrane is composed of cholesterol oxidase enzyme and polymerization mixture; which holds paramount influence on the properties of the cholesterol biosensor. The presented biosensor reveals an appreciable reproducibility, good selectivity and high sensing capability with a linear slope curve of ∼64 mV per decade. The strong biocompatibility among stabilized polymeric lipid membranes and human biofluids provides the possibility to use for real blood samples and other biological applications. © 2013 Versita Warsaw and Springer-Verlag Wien.
cited By 18